2010
DOI: 10.1038/npp.2010.126
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Responses to Monetary Outcomes in Cortex, but not in the Basal Ganglia, in Schizophrenia

Abstract: Psychosis has been associated with aberrant brain activity concurrent with both the anticipation and integration of monetary outcomes. The extent to which abnormal reward-related neural signals can be observed in chronic, medicated patients with schizophrenia (SZ), however, is not clear. In an fMRI study involving 17 chronic outpatients with SZ and 17 matched controls, we used a monetary incentive delay (MID) task, in which different-colored shapes predicted gains, losses, or neutral outcomes. Subjects needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
141
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(174 citation statements)
references
References 60 publications
25
141
5
1
Order By: Relevance
“…[19][20][21][22] In contrast, there is now meta-analytic support for reduced VS activation in patients with established schizophrenia, 24 but results on the individual study level are very inconsistent. 15,16,23,25,31,35,59,62,63 These mixed findings support the notion that striatal alterations in psychosis do not solely consist of hypo-activation but vary between different stages (early vs chronic) and different forms of psychosis (schizophrenia vs non-schizophrenia). In line with this notion, patients with FEP-SZ showed higher striatal activity compared to other individuals within the psychosis continuum.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…[19][20][21][22] In contrast, there is now meta-analytic support for reduced VS activation in patients with established schizophrenia, 24 but results on the individual study level are very inconsistent. 15,16,23,25,31,35,59,62,63 These mixed findings support the notion that striatal alterations in psychosis do not solely consist of hypo-activation but vary between different stages (early vs chronic) and different forms of psychosis (schizophrenia vs non-schizophrenia). In line with this notion, patients with FEP-SZ showed higher striatal activity compared to other individuals within the psychosis continuum.…”
Section: Discussionsupporting
confidence: 69%
“…52 At the neural level, the observed positive correlation of apathy and increased VS activity contrasts with previous studies, including our own, reporting a negative association in patients with schizophrenia. 25,26,35 However, the studies showing an association of striatal hypoactivation and apathy were typically based on samples with more primary negative symptoms in patients with chronic schizophrenia. 25,26 In contrast, the current study investigated a psychosis continuum from nonclinical participants to patients with early psychosis with a different psychopathological construct of apathy (partly secondary to positive and depressive symptoms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies investigated the dopamine model-related brain response in psychiatric disorders, such as depression (Kumar et al, 2008) or schizophrenia (Waltz et al, 2010), and tended to find reduced brain response in those disorders. Dopamine neuronal reward response can be captured in an algorithm that takes advantage of dopamine neurons responding to unexpected reward stimulus receipt or omission (Schultz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While in contrast, chronic cannabis users are found to exhibit exaggerated right ventral striatum activation during the anticipation of incentives (Nestor, et al, 2010). On the other hand, following informative feedback relevant to reinforcement outcome, activation of reward-related brain circuitry to monetary gain is found to be increased in patients with ADHD (Ströhle et al, 2008) and substance dependent patients (Bjork, et al, 2008); while activation of reward related brain areas in patients with schizophrenia (Waltz, et al, 2010), patients with autism spectrum disorder (Dichter, et al, 2012) and patients with major depressive disorder (Pizzagalli, et al, 2009) is found to be decreased. The differences between and within mental disorders in the activation of reward-related brain regions during anticipatory and reward receipt stages underscore the importance of using tasks like the fMRI MID to dissociate the neural response associated with each stage of reinforcement processing.…”
mentioning
confidence: 99%